2022
DOI: 10.34190/ejbrm.20.1.2196
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Common Method Variance via Experimental Conditions

Abstract: Research data collected from single respondents may raise concerns regarding common method variance (CMV), which is believed to threaten the validity of findings. The primary concern is that CMV can inflate substantive relationships, such that they appear statistically significant when they are not. Thus, understanding the nature of CMV is critical, especially when one considers the popularity—and sometimes necessity—of using self-report data. Research examining CMV has found conflicting evidence about the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Common method bias is also the case when a researcher creates estimates of validity and reliability that may lead a researcher to believe that a scale does not accurately reflect an implicit measure but does so accurately. Such an error may cause common method bias in future meta-analysis studies ( Wall, 2014 ). As a result, the studies included in the meta-analysis were examined and it was seen that the data collection tools used were suitable for the purpose of the studies, and the validity and reliability information was presented.…”
Section: Methodsmentioning
confidence: 99%
“…Common method bias is also the case when a researcher creates estimates of validity and reliability that may lead a researcher to believe that a scale does not accurately reflect an implicit measure but does so accurately. Such an error may cause common method bias in future meta-analysis studies ( Wall, 2014 ). As a result, the studies included in the meta-analysis were examined and it was seen that the data collection tools used were suitable for the purpose of the studies, and the validity and reliability information was presented.…”
Section: Methodsmentioning
confidence: 99%
“…The two-phase survey comprised previously empirically validated instruments. The study also included a latent marker variable (Williams et al , 2010) that had been previously used with the survey of SPOS and JES (Jones, 2015; Wall, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…CFA marker. The attitude toward the color blue measure (Miller and Chiodo, 2008) is an eight-item scale developed specifically to be used as a latent marker variable (Williams et al , 2010) and has previously been used alongside the SPOS and JES (Jones, 2015; Wall, 2014). Respondents rate each question on a seven-point Likert-type scale ranging from “strongly disagree” to “strongly agree.” Sample items include “I prefer blue to other colors” and “I think blue cars are ugly.” Cronbach’s alpha was 0.84 in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…items and guaranteeing respondent anonymity (Podsakoff et al, 2003;Podsakoff & Organ, 1986), these potential remedies have been rarely studied empirically, and the small amount of research that addresses them has shown little in the way of efficacy (Castille et al, 2017;Wall et al, 2015). In contrast, post hoc efforts at detecting CMV have been studied more extensively.…”
mentioning
confidence: 99%